Correlation of trace element composition of oils and other caustobiolites with chemical content of different types of biota and the Upper, Middle and the Lower Earth’s Crust - V., Rodkin M.; Lu, Ngo Thi; A., Punanova S. (Vietnam Journal of Earth Sciences, 2020)
The trace element (TE) content of oils is known to have a polygenetic character and to be inherited from an organic matter, surrounding rocks and from formation waters. The presence of some TEs indicates the involvement of the deep source, at least from the Lower Crust. However, these conclusions have a qualitative character. We present the results of the correlation analysis of TE content of oils with the chemical compositions of the Upper, Middle, and Lower Crust, with different types of organic matter, clays, and causetobiolites. A logarithmic instead of a linear scale for TE concentration values are used in calculations because the examining values change by several orders of magnitude. The TE compositions of clays, coals, and shales correlate better with the composition of the upper continental crust and an organic matter. In contrast, the TE contents in the majority of oils correlate stronger with the Lower crust, which indicates a significant contribution from the Lower continental crust. This finding points to the role that the uprising flow of fluid plays in the process of the formation of oil. Only young oils from Kamchatka and from White Tiger huge oil fields indicate a better correlation with the Upper crust. This finding is explained by the lower depth of formation of the uprising flow of deep waters because of higher deep temperatures in Kamchatka and in the White Tiger oil field area. The obtained trend of change of TE content in clays and different caustobiolites oils including is interpreted as a mixing line between the subsurface end member (which is characterized by high correlation with the chemical content of the Upper crust and biota) and the deep end member (high correlation with the chemical content of the Lower crust).